Enzymatic validation of species‐specific protocols for metal subcellular fractionation in freshwater animals. (24th August 2018) - Cardon, Pierre‐Yves; Caron, Antoine; Rosabal, Maikel; Fortin, Claude; Amyot, Marc
Abstract: The use of fractionation protocols to determine metal subcellular distribution in aquatic organisms has gained much interest over the last 15 yr, however, accurate separations among the different components of cells are challenging. Subcellular fractions separated with such an approach are operationally defined and a potentially significant difference can exist between anticipated and resulting fractions. This study customizes and validates subcellular partitioning protocols, for three different freshwater organisms representing a diversity of challenges for subcellular fractionation: Daphnia magna, Chironomus riparius, and liver of Oncorhynchus mykiss . Several protocols involving different homogenization methods, centrifugation speeds, or conservation conditions were tested, and their efficiencies were assessed using enzymatic biomarker assays. Our work allowed us to identify critical steps to improve separations. First, for D. magna, a crustacean with a reinforced chitinous exoskeleton, the use of a strong homogenization method using a sonicator is necessary. Second, for both invertebrates, we observed the leaking of the mitochondrial matrix during cell fractionation, regardless of the homogenization strength and conservation conditions. Therefore, we propose that the mitochondria fraction should be referred to as the mitochondrial membrane fraction, and the cytosol fraction should be identified as the cytosol and mitochondrial matrix fraction. Third, the presence of a lipid‐rich layer during O. mykiss liver fractionation may lead to an overlap between mitochondria and cytosol and must be considered in the protocol development. Finally, lysosomes should not be pooled with the microsomes fraction without prior validation. Overall, this study provides a benchmark for future methodological studies on similar taxa.